(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article deals with the patterns and dynamics of the formation of smart cities and describes the problems and prospects of the mechanisms of formation of smart cities in the world and in Ukraine. The purpose of the work is to compare the main achievements in the implementation of smart cities in Ukraine and in the world, in particular, on the example of the European Union countries, where today there are about several innovative models of smart cities. That is why, on the example of intelligent cities of the EU, Ukrainian cities should actively borrow experience and make every effort to develop a strategy for the introduction of an innovative model of a smart city